2015
DOI: 10.1111/cdev.12466
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Electroencephalogram Asymmetry and Temperament Across Infancy and Early Childhood: An Exploration of Stability and Bidirectional Relations

Abstract: The stability of frontal electroencephalogram (EEG) asymmetry, temperamental activity level and fear, as well as bidirectional relations between asymmetry and temperament across the first four years of life were examined in a sample of 183 children. Children participated in annual lab visits through 48 months, providing EEG and maternal report of temperament. EEG asymmetry showed moderate stability between 10 and 24 months. Analyses revealed that more left asymmetry predicted later activity level across the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 78 publications
2
42
1
Order By: Relevance
“…Fear—at least of the type elicited by a stranger approach—is thought to emerge around 6 months of age (Waters, Matas, & Sroufe, ) and increase through age 36 months (Brooker et al, ; Sroufe, ). Unfortunately, the timing of developing positive affect in early infancy has received scant research attention, and the direction of developing associations between EEG asymmetry and affect are only beginning to be investigated (Howarth et al, ). Moreover, the possibility of vast individual differences in the differentiation of emotions (Barrett, Gross, Conner Christensen, & Benvenuto, ) may also lead to inconsistencies in patterns of physiological arousal during different emotion‐eliciting episodes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fear—at least of the type elicited by a stranger approach—is thought to emerge around 6 months of age (Waters, Matas, & Sroufe, ) and increase through age 36 months (Brooker et al, ; Sroufe, ). Unfortunately, the timing of developing positive affect in early infancy has received scant research attention, and the direction of developing associations between EEG asymmetry and affect are only beginning to be investigated (Howarth et al, ). Moreover, the possibility of vast individual differences in the differentiation of emotions (Barrett, Gross, Conner Christensen, & Benvenuto, ) may also lead to inconsistencies in patterns of physiological arousal during different emotion‐eliciting episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Stability in asymmetry across longer periods (2-3 months) was generally apparent only after 9 months of age. Similarly, Howarth, Fettig, Curby, and Bell (2016) reported moderate stability in asymmetry from 10 to 24 months of age and limited stability between 24 and 36 months. Such findings illustrate the need to systematically compare levels of short-and long-term stability in frontal asymmetry measures across the first year of life.…”
Section: Introductionmentioning
confidence: 92%
“…We examined positive affectivity and fearfulness in a growth modeling context, as these individual differences represent affective components of approach and avoidance motivational–neurobehavioral systems (Diaz & Bell, ; Gray, ; Hane, Fox, Henderson, & Marshall, ), directing behavioral and emotional responses in tandem (Fox, Henderson, Rubin, Calkins, & Schmidt, ). Alongside stability, significant developmental shifts have been noted in approach–avoidance tendencies, including their neurophysiological correlates (Howarth, Fettig, Curby, & Bell, ). These transitions are consistent with the view of temperament as developing reactive and regulatory tendencies, with especially rapid changes in early childhood (Rothbart, ).…”
mentioning
confidence: 99%
“…However, whether and how such developmental change affects frontal asymmetry remains unclear (Saby & Marshall, 2012). Studies investigating the stability of frontal asymmetry throughout childhood have observed limited stability (Howarth, et al, 2016;Vuga, Fox, Cohn, Kovacs, & George, 2008), suggesting that developmental changes take place. Finally, with respect to the relation between frontal asymmetry and approach-withdrawal motivation and behavior, expected associations between frontal asymmetry and its theorized behavioral antecedents and consequences have not always been found (see, e.g., Peltola et al, 2014).…”
Section: Discussionmentioning
confidence: 99%